KEIKUTSERTAAN KEPALA KELUARGA DESA TEGALSARI PONOROGO DALAM JAMINAN KESEHATAN NASIONAL - Mahayasa Adiputra; Alfred Mulana; Ika Farmani (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2017)
Member of National Health Incurance (JKN) has the obligation to pay contributions themselves, therefore requires an understanding of JKN. That in mind people to participate in JKN. There are many contributing factors that include family heads themselves and their family participate in member of JKN. These factors include the knowledge, attituade, information obtained, and family support. BPJS target JKN coverage in 2019 to be 100%.. The objective of this research to show the factors its relation with community participations in national health insurance at Tegalsari region of Ponorogo. Thisresearch uses observatoinal study with case control approach. The populations for Tegalsari region head of family who had participated in JKN Mandiri are 149 participants. The chosen sample through proportinate and simple random sampling is 134 participants for casus and 134 no participant for control. Statistic test uses chi square. Base on the result, there is relation between knowledge and participation in JKN (p=0,000), relation between attitude and participation in JKN (P=0,002), relation between information obtained and partipation in JKN (p=0,026), relation between family support and participation in JKN (p=0,000, relation between income and participation in JKN (p=0,027)